Lactobacillus rhamnosus GR-1 Alleviates Escherichia coli-Induced Inflammation via NF-κB and MAPKs Signaling in Bovine Endometrial Epithelial Cells - Liu, Jiawei; Feng, Xiaowei; Li, Botong; Sun, Yan; Jin, Tianxiong; Feng, Mingque; Ni, Yaodi; Liu, Mingchao (Frontiers in Cellular and Infection Microbiology, 2022)
Escherichia coli is one of the predominant pathogens that causes endometritis in dairy cows, which decreased the economic benefits of dairy farming seriously. Probiotic consumption has been reported to impart beneficial effects on immunomodulation; however, the inflammatory regulation mechanism of probiotic on endometritis in dairy cows remains unexplored. This study was conducted to reveal the mechanism of Lactobacillus rhamnosus GR-1 (L. rhamnosus GR-1) against bovine endometrial epithelial cells (BEECs) inflammatory injury induced by E. coli. The model of cellular inflammatory injury was established in the BEECs, which from the healthy dairy cows’ uterus, using E. coli. The effect of L. rhamnosus GR-1 addition on inflammation was evaluated in BEECs with E. coli-induced endometritis. The underlying mechanisms of anti-inflammation of by L. rhamnosus GR-1 were further explored in E. coli-stimulated BEECs. The results showed that use L. rhamnosus GR-1 alone could not cause the change of inflammatory factors, but L. rhamnosus GR-1 could significantly alleviate the expression of E. coli-induced inflammatory factors. Further study revealed that L. rhamnosus GR-1 significantly inhibited the TLR4 and MyD88 expression stimulated by E. coli. Moreover, we observed that L. rhamnosus GR-1 could inhibit the expression of NF-κB and MAPKs-related pathway proteins in BEECs induced by E. coli. In conclusion, L. rhamnosus GR-1 can effectively protect against E. coli-induced inflammatory response that may be closely related to the inhibition of TLR4 and MyD88 stimulating NF-κB and MAPKs.